P5_1 How Far Did Gandalf Fly... You Fools? - Sharman, Mark; Knott, George; Rayson, Ben; Molloy, David (Physics Special Topics, 2022)
In the Lord of the Rings, there is an infamous scene in which Gandalf fights the Balrog of Moria, ultimately causing the pair to fall from the bridge of Khazad-Dûm. This report contains the fundamental physics required to establish the height at which Gandalf fell and whether he could have survived. The necessary calculations are carried out in Python using an iterative model to continually update position and velocity values, providing the most accurate result. Using this model we were able to arrive at a bridge height of 3900m and decided it would be possible for him to survive this fall.